ADAPTACIÓN DE LA CEPA MUNANTA DE TRYPANOSOMA CRUZI AL CULTIVO IN VITRO EN CÉLULAS VERO - Velazco Gamboa, Carolina; Departamento de Microbiología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2013)
The importance of obtaining the different stages of Trypanosoma cruzi in order to recognize the antigens involved in the intracellular invasion and replication processes, makes it necessary to adapt these strains to tissue culture, especially considering the high leve! of biological, biochemical and genetic variation, which is found among the strains and clones ofthe parasite. Within the aforementioned context, in this study, the Colombian strain ofT. cruzi, M un anta, was adapted to tissue culture in Yero Cells, obtaining the principal forms ofthe parasite: trypomastigotes, amastigotes and epimastigotes. lt was observed that the liberation of the trypomastigotes occurred on the seventh day postinfection and the quantity obtained was directly proportional to the number of infecting parasites. On the other hand, the majority of the trypomastigotes observed 48 hours after washing the monolayer five days after infection, were had thick-looking shapes corresponding to the initiation ofthe trasforrnation from trypomastigotes to amastigotes.